2014
DOI: 10.1007/bf03397040
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Computer-Based Reading Activities and Reading Achievements among Hong Kong and U.S. Students: A Comparative Study Using PIRLS 2011 Data

Abstract: Reading for personal interest and acquiring and using information using various reading processes are important parts of reading literacy that students need to develop in order to progress successfully through their schooling and fully function in the information society. Computer assisted reading instructional activities are assumed useful in improving the reading literacy of students, especially reading processes. However, students in Hong Kong and the US demonstrated a substantial performance gap in reading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…For example, a study in Science in 2011 reported that search engines made searching for information so easy that people tend to have low recall of difficult questions when primed to think of being able to seek for help from computers (Sparrow, Liu, & Wegner, 2011). Basic language skills, such as reading and writing, are impaired due to the fact that people engage in less handwriting or more reading and writing on the computer (Li & Wang, 2014;Tan, Xu, Chang, & Siok, 2013).…”
Section: Help Doctors To Use Technologies Optimally In the Futurementioning
confidence: 99%
“…For example, a study in Science in 2011 reported that search engines made searching for information so easy that people tend to have low recall of difficult questions when primed to think of being able to seek for help from computers (Sparrow, Liu, & Wegner, 2011). Basic language skills, such as reading and writing, are impaired due to the fact that people engage in less handwriting or more reading and writing on the computer (Li & Wang, 2014;Tan, Xu, Chang, & Siok, 2013).…”
Section: Help Doctors To Use Technologies Optimally In the Futurementioning
confidence: 99%